2015
DOI: 10.1371/journal.pone.0119914
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Is Associated with Physical Performance in Suburb-Dwelling Older Chinese: A Cross-Sectional Study

Abstract: BackgroundPhysical performance is reported to have various beneficial effects on human health, especially in older individuals. Although such effects are associated with body mass index (BMI), the relationship between BMI and physical performance has not been clarified.DesignWe conducted a cross-sectional study of 966 suburb-dwelling Tianjin individuals aged ≥ 60 years (average age 67.5±6.02, men 435, women 531). Mobility, balance, and muscle strength were assessed by walking speed, timed up-and-go test (TUGT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
0
13
0
6
Order By: Relevance
“…We included age and gender as predictors in our model because our group’s previous studies have found that age might be an important factor in affecting balance among women. 23 Also a systematic review has found that standardization of testing conditions along with control of significant potential confounders (age and gender) would provide better information about the predictive value of TUGT to measure future falls in older adults. 8 Among the three groups, recurrent fallers were most likely to be female and the oldest of the participants ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…We included age and gender as predictors in our model because our group’s previous studies have found that age might be an important factor in affecting balance among women. 23 Also a systematic review has found that standardization of testing conditions along with control of significant potential confounders (age and gender) would provide better information about the predictive value of TUGT to measure future falls in older adults. 8 Among the three groups, recurrent fallers were most likely to be female and the oldest of the participants ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study estimated the benefits of physical activity in class 3 GRP who used "role-playing games" during breaks, recording a decrease in the BMI relative to best athletic performance in the post-test. Similarly, it was admitted as an energy indicator relating to total mass and height, which allows the comparison of athletes in various health or fitness tests (20). It was labelled by preventive studies as resulting into less body fat and into the most appropriate profile in terms of body conditions so as to realize an optimal performance (12).…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were as follows: (1) age < 60 years, (2) severe arthritis or joint deformity causing impaired mobility or localized loss of strength, (3) malignancy, (4) current use of androgens or antiandrogens, and (5) refusal to participate in this study. 15 In addition, 299 participants were excluded from the analysis because performance-based assessment was not performed or metabolic health and obesity indicators were missing. In the end, 1395 older participants (men 571, women 824) were available for analysis.…”
Section: Methodsmentioning
confidence: 99%